Acute fatigue impairs neuromuscular activity of anterior cruciate ligament-agonist muscles in female team handball players - Zebis, M. K.; Bencke, J.; Andersen, L. L.; Alkjaer, T.; Suetta, C.; Mortensen, P.; Kjaer, M.; Aagaard, P. (Scandinavian Journal of Medicine & Science in Sports, 2011)
In sports, like team handball, fatigue has been associated with an increased risk of anterior cruciate ligament (ACL) injury. While effects of fatigue on muscle function are commonly assessed during maximal isometric voluntary contraction (MVC), such measurements may not relate to the muscle function during match play. The purpose of this study was to investigate the effect of muscle fatigue induced by a simulated handball match on neuromuscular strategy during a functional sidecutting movement, associated with the incidence of ACL injury. Fourteen female team handball players were tested for neuromuscular activity [electromyography (EMG)] during a sidecutting maneuver on a force plate, pre and post a simulated handball match. MVC was obtained during maximal isometric quadriceps and hamstring contraction. The simulated handball match consisted of exercises mimicking handball match activity. Whereas the simulated handball match induced a decrease in MVC strength for both the quadriceps and hamstring muscles (P<0.05), a selective decrease in hamstring neuromuscular activity was seen during sidecutting (P<0.05). This study shows impaired ACL-agonist muscle (i.e. hamstring) activity during sidecutting in response to acute fatigue induced by handball match play. Thus, screening procedures should involve functional movements to reveal specific fatigue-induced deficits in ACL-agonist muscle activation during high-risk phases of match play.